Understanding the Preferred Crystal Orientation of Sputtered Silver in Ar/N2 Atmosphere: A Microstructure Investigation - YuHao Hu; Jiajun Zhu; Chao Zhang; Wulin Yang; Licai Fu; Deyi Li; Lingping Zhou (Advances in Materials Science and Engineering)
Silver thin films were prepared by direct current (DC) magnetron sputtering technique in Ar/N2 atmosphere with various N2 volumetric ratios on Si substrates. Silver thin films prepared in pure Ar atmosphere show highly (111) preferred orientation. However, as the N2 content increases, Ag (111) preferred orientation evolves into (100) preferred orientation gradually. When N2 content is more than 12.5 vol.%, silver thin films exhibit highly (100) preferred orientation. Moreover, the average grain size decreases with increasing N2 content. Silver thin films with low relative density are prepared at high N2 content, which results in higher resistivity of films. By analyzing the resistivity and microstructures of silver thin films, the optimum range of N2 content to get compact silver thin films is found to be not more than 33.3 vol.%. Finally, the mechanism of N2 addition on microstructure evolution of silver thin films was proposed.